PERANAN DINAS KEBUDAYAAN DAN PARIWISATA KOTA BANDUNG UNTUK MENINGKATKAN WISATA MICE DI KOTA BANDUNG - , SALMAN MUTTAQIN PATRAJAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bandung actually has open oppurtunities in developing MICE tourism but the oppurtunities that would be meaningless if the Bandung city tourism being offset by a number of strategic step to seize this great MICE oppurtunities. Role of government agencies that culture and tourism department is necessary because the government is an agencies that issued certain policies in developing and prosperous nation. Techniquesz of data analysis were used to analyze the problem is descriptive qualitative, by describing the studied conditions with systemically and through this method to analyze the object in the form of description and explanation. It can be conclude that the role of Bandung culture and tourism department to improve MICE tourism is sufficient in accordance with the policies published by local regulations, both in terms of the promotion, development of inter-regional approaches and strategies of approach.